Perceptions and deflections: Associations between attitudes towards people with hepatitis C and testing for hepatitis C among Australian gay and bisexual men - Brener, L.; Ellard, J.; Murphy, Dean; Callander, D. (2013)
Background Research indicates that the incidence of hepatitis C (HCV) among HIV-positive men who have sex with men (MSM) is increasing. Although injecting drug use remains the predominant means of transmission of HCV in the developed world, there is evidence of sexual transmission of HCV among MSM. Stigma associated with HCV has been shown to negatively impact HCV testing and health-seeking behaviour. There is little research that addresses attitudes towards HCV testing among this population. Methods: The current exploratory study focussed on HCV knowledge, HCV testing, sexual practices, perceptions of HCV risk and attitudes towards people with HCV among Australian MSM. The sample consisted of 590 men who completed an online survey. Results: The findings suggest that attitudinal factors related to HCV were associated with HCV testing behaviour. The more negatively respondents felt about people with HCV, the less likely they were to have ever had an HCV test. Behavioural risk factors related to sexual practices (i.e. is condom use and sexual risk activities) were not associated with HCV testing. Testing for HCV was associated with HIV-positive status, more knowledge about HCV and a greater likelihood of ever having injected drugs. Conclusions: The attitudes of MSM towards those who inject drugs are negative, mirroring that of society more generally. Furthermore, these attitudes, coupled with a lack of knowledge of the risk of sexual transmission of HCV among gay men, especially those who are HIV-positive, may act to prevent routine HCV testing among some MSM at potential risk of acquiring HCV. © CSIRO 2013.